In vivo estimation of transverse relaxation time constant (T2) of 17 human brain metabolites at 3T. Issue 2 (17th January 2018) - Wyss, Patrik O.; Bianchini, Claudio; Scheidegger, Milan; Giapitzakis, Ioannis A.; Hock, Andreas; Fuchs, Alexander; Henning, Anke
Abstract : Purpose: The transverse relaxation times T2 of 17 metabolites in vivo at 3T is reported and region specific differences are addressed. Methods: An echo‐time series protocol was applied to one, two, or three volumes of interest with different fraction of white and gray matter including a total number of 106 healthy volunteers and acquiring a total number of 128 spectra. The data were fitted with the 2D fitting tool ProFit2, which included individual line shape modeling for all metabolites and allowed the T2 calculation of 28 moieties of 17 metabolites. Results: The T2 of 10 metabolites and their moieties have been reported for the first time. Region specific T2 differences in white and gray matter enriched tissue occur in 16 of 17 metabolites examined including single resonance lines and coupled spin systems. Conclusion: The relaxation time T2 is regions specific and has to be considered when applying tissue composition correction for internal water referencing. Magn Reson Med 80:452–461, 2018. © 2018 International Society for Magnetic Resonance in Medicine.